Lower affective empathy in oral contraceptive users: a cross-sectional fMRI study. (23rd September 2022) - Kimmig, Ann-Christin Sophie; Wildgruber, Dirk; Gärtner, Anna; Drotleff, Bernhard; Krylova, Marina; Lämmerhofer, Michael; Sundström-Poromaa, Inger; Derntl, Birgit
Abstract: Evidence accumulates that oral contraceptive (OC) use modulates various socio-affective behaviors, including empathic abilities. Endogenous and synthetic sex hormones, such as estrogens and progestogens, bind to receptor sites in brain regions (i.e. frontal, limbic, and cerebellar) involved in socio-affective processing. Therefore, the aim of this study was to investigate the role of OC use in empathy. In a cross-sectional functional magnetic resonance imaging study, women in different hormonal states, including OC use ( n  = 46) or being naturally cycling in the early follicular (fNC: n  = 37) or peri-ovulatory phase (oNC: n  = 28), performed a visual, sentence-based empathy task. Behaviorally, OC users had lower empathy ratings than oNC women. Congruently, whole-brain analysis revealed significantly larger task-related activation of several brain regions, including the left dorsomedial prefrontal gyrus (dmPFG), left precentral gyrus, and left temporoparietal junction in oNC compared to OC women. In OC users, the activity of the left dmPFG and precentral gyrus was negatively associated with behavioral and self-reported affective empathy. Furthermore, empathy-related region-of-interest analysis indicated negative associations of brain activation with synthetic hormone levels in OC women. Overall, this multimodal, cross-sectional investigation of empathy suggests a role of OC intake in especially affective empathy and highlights the importance of including synthetic hormone levels in OC-related analyses.